2019
DOI: 10.1016/j.jclepro.2019.04.111
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions and heavy metal contamination analysis of stone mastic asphalt mixtures produced with high rates of different waste materials

Abstract: The incorporation of waste materials in asphalt mixtures has driven several studies mainly focused on improving their mechanical performance while minimizing the use of virgin materials. However, these could only be considered cleaner solutions for road paving works if their production and application do not present additional risks for human health and the environment. Therefore, this study aims at assessing the carbon dioxide emissions and possible leachates of stone mastic asphalt mixtures produced with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, due to the mineral skeleton (gap-graded conformed by two parts of coarse aggregate) of the SMAs, it is required to incorporate a stabilizer additive to prevent the drain-down phenomena [56,57]. The inclusion of the stabilizing agent can cause SMA to generate a higher environmental burden than conventional HMA mixtures [58]. In this study, crumb rubber was used as the stabilizing additive.…”
Section: Functional Unitmentioning
confidence: 99%
“…Nevertheless, due to the mineral skeleton (gap-graded conformed by two parts of coarse aggregate) of the SMAs, it is required to incorporate a stabilizer additive to prevent the drain-down phenomena [56,57]. The inclusion of the stabilizing agent can cause SMA to generate a higher environmental burden than conventional HMA mixtures [58]. In this study, crumb rubber was used as the stabilizing additive.…”
Section: Functional Unitmentioning
confidence: 99%
“…After the calculation of optimum design thickness for the surface courses for each type of mixes, the amount of material needed to construct 1 km of two-lane (7 m) surface course was calculated. e standard amount of emission (in terms of kg of CO 2 equivalent) by different materials (coarse and fine aggregates, stone dust (SD), hydrated lime (HL), and asphalt binder) was taken from the several previously published peer reviewed studies [58][59][60][61]. European Union's Waste Framework Directive (2008/98/EC) defines "waste" as any substance or object which the holder discards or intends or is required to discard [62].…”
Section: Analysis Of Global Warming Potential (Gwp) Of Designed Surface Courses According To Intergovernmentalmentioning
confidence: 99%
“…There is a possibility of the pavement releasing plastic particles, from a few nanometers to 5 mm in dimension [10], which can be harmful to human and other species' health [11]. These issues associated with microplastic are still under evaluation by the scientific community [12,13]. Despite that, it must be emphasized that several studies identified the presence of microplastics in road dust from different sources even when asphalt materials do not incorporate plastic waste [14][15][16].…”
Section: Introductionmentioning
confidence: 99%